A chromatin-linked CPL2–PHD2/3 module sustains multiple DNA methylation pathways and Polycomb silencing - Lingrui Zhang; Kai Tang; Tiandan Long; Li-Li Zhang; Peipei Zhu; Fuhua Fan; Jianxin Fu; Chao Zhang; Jian-Kang Zhu (Proceedings of the National Academy of Sciences, 2025)
While multiple chromatin-based epigenetic pathways are well characterized, their genome-wide coordination and hierarchical interplay remain poorly understood. We previously identified the BAH–PHD–CPL2 complex, where AIPP3 binds H3K27me3 via its BAH domain and, in concert with PHD2 and PHD3 (PHD2/3), recruits CPL2 to repress transcription by dephosphorylating RNA Polymerase II. Here, we show that CPL2 and PHD2/3 form a distinct module (CPL2–PHD2/3) that safeguards CHH DNA methylation and silences CHH-methylated sites at transposable elements (TEs) through engagement of multiple DNA methylation pathways. The CPL2–PHD2/3 module physically associates with SUVH4 and SUVH5 (SUVH4/5) to preserve SUVH4/5–CMT2-mediated CHH methylation at a subset of H3K9me2-marked regions. Chromatin enrichment of PHD3 likewise enables the module to sustain RNA-directed DNA methylation (RdDM)-mediated CHH DNA methylation at sites bearing H3K9me2, H3K27me3, or neither. Thus, CPL2–PHD2/3 emerges as a previously underappreciated, multifunctional regulator of plant DNA methylation networks. Unexpectedly, its gene repression function is uncoupled from DNA methylation. CPL2–PHD2/3 represses Polycomb-marked genes by interacting with LHP1 or recognizing hypomethylated H3K4. While it cooperates with LHP1 at a subset of targets, it also independently silences many more genes that LHP1 alone cannot repress, both sets of genes being critical for proper development. This dual, yet largely LHP1-insufficient, repression mode singles out CPL2–PHD2/3 as the essential executor of Polycomb silencing. Together, our findings establish CPL2–PHD2/3 as a chromatin-responsive integrator that spans DNA methylation and Polycomb-associated repression, providing a unifying mechanism for epigenetic control of both TEs and genes across diverse chromatin landscapes.